2000
DOI: 10.3141/1714-03
|View full text |Cite
|
Sign up to set email alerts
|

Water-Quality Effects of Tire Shreds Placed Above the Water Table: Five-Year Field Study

Abstract: A field trial was constructed beneath a secondary state highway in North Yarmouth, Maine, to investigate the water-quality effects of tire shred fills placed above the groundwater table. Samples were collected in three 3-m2 geomembrane-lined basins located beneath the shoulder of the road. Two of the basins are overlaid by 0.61 m of tire shreds with a 75-mm maximum size topped by 0.72 to 1.37 m of granular soil. The third basin serves as a control and is overlaid by only 0.72 m of granular soil. Quarterly samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 1 publication
0
30
0
5
Order By: Relevance
“…Humphrey and Katz (2000) and Humphrey and Katz (2001) monitored effluents, and the results indicated that toxic compounds had no significant adverse effects on ground water quality above or below the water table over a period of 5 years. O'Shaughnessy and Garga (2000b) and Yoon et al (2004b) obtained results showing that waste tires are harmless, because steel wires which may provide adverse effect to water quality or soil are covered by vulcanized rubber or polymer material.…”
Section: Waste Tires As Soil Reinforcement Materialsmentioning
confidence: 96%
“…Humphrey and Katz (2000) and Humphrey and Katz (2001) monitored effluents, and the results indicated that toxic compounds had no significant adverse effects on ground water quality above or below the water table over a period of 5 years. O'Shaughnessy and Garga (2000b) and Yoon et al (2004b) obtained results showing that waste tires are harmless, because steel wires which may provide adverse effect to water quality or soil are covered by vulcanized rubber or polymer material.…”
Section: Waste Tires As Soil Reinforcement Materialsmentioning
confidence: 96%
“…Construction of landfill LCRS's drainage layer using waste tire chips instead of natural aggregates may be both environmentally and economically beneficial (Humphrey and Manion 1992;Ahmed and Lovell 1993;Edil and Bosscher 1994;Adyilek et al 2006;Hudson et al 2007;ASTM 2008;Humphrey 2011;Kaushik et al 2012). Most of the existing work showed that scrap tires shreds did not cause groundwater/surface water contamination, since the measured concentrations of constituents leached from the tires were significantly below the USEPA maximum concentration limits (Humphrey and Katz 2001;Park et al 2003). Additional advantages of using tire shreds as demonstrated by performing sorption/desorption tests by Park et al (2003) using trichloroethylene and toluene (as contaminates in aqueous solution) indicated that tire rubber sorb up to 5.6 % of the sorption capacity of the granular activated carbon on volume basis.…”
Section: Lcrsmentioning
confidence: 98%
“…Leaching (Han 1993;Humphrey and Katz 2000), separation of rubber and asphalt binder (Kim et al 2007;Shu and Huang 2014), emission during hot-mixing (Stroup-Gardiner and Wattenberg-Komas 2013g), recyclability (Han 1993) etc. are some of the issues identified by the researchers, specific to various types of mixes…”
Section: Tyre Scrap Rubbermentioning
confidence: 99%